The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fonc.2022.913217
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Effectively Cures a Patient With Severe Bleeding Immune Checkpoint Inhibitor-Associated Colitis and a Short Review

Abstract: Immune checkpoint inhibitors (ICIs) have opened up a new way for tumor therapy but simultaneously led to the occurrence of immune-related adverse events. We report a case of successful treatment of PD-1 inhibitor-associated colitis with fecal microbiota transplantation (FMT). The patient was a palatal malignant melanoma who developed diarrhea and hematochezia accompanied by fever, gastrointestinal bleeding, and infection after the third treatment with PD-1 (Toripalimab). The patient received general treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…The second patient had a decrease of all the T cell subtypes following FMT; however, the CD4 + T cell population was relatively unchanged compared to the CD8 + T cells, which was associated with the persistence of T reg cells in the colonic mucosa. In another recent case study ( 143 ), a patient suffering from palatal malignant melanoma developed severe ICI-associated colitis after the third dose of anti-PD-1 treatment. After unsuccessful treatment with corticosteroids, an FMT was administered to successfully resolve colitis symptoms.…”
Section: Section 5: Microbiome-based Therapies Acting On the Immune S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The second patient had a decrease of all the T cell subtypes following FMT; however, the CD4 + T cell population was relatively unchanged compared to the CD8 + T cells, which was associated with the persistence of T reg cells in the colonic mucosa. In another recent case study ( 143 ), a patient suffering from palatal malignant melanoma developed severe ICI-associated colitis after the third dose of anti-PD-1 treatment. After unsuccessful treatment with corticosteroids, an FMT was administered to successfully resolve colitis symptoms.…”
Section: Section 5: Microbiome-based Therapies Acting On the Immune S...mentioning
confidence: 99%
“…After unsuccessful treatment with corticosteroids, an FMT was administered to successfully resolve colitis symptoms. The patient’s clinical outcome was associated with decreased fecal calprotectin and restoration of the congested, inflamed colonic mucosa to near normal level ( 143 ). These mucosal immune changes reported in the case reports suggest that FMT is signaling to reshape intestinal immune cell populations resulting in therapeutic effect against ICI-associated colitis.…”
Section: Section 5: Microbiome-based Therapies Acting On the Immune S...mentioning
confidence: 99%
“…Convincing, if complex, association between the gut microbiome and cancer outcomes in CPI recipients has emerged ( 37 , 38 ). Moreover, case reports have demonstrated faecal microbiota transplant (FMT) can mitigate both anti-PD-1 tumour-resistance and treatment-refractory GI-irAEs ( 39 , 40 ), and antibiotic therapy is correlated with high-grade GI-irAE incidence ( 41 ) – all consistent with a critical immune-mediating role for the microbiome in this setting that has yet to be properly understood ( 42 ).…”
Section: Gastrointestinal Iraesmentioning
confidence: 99%
“…Similarly, the enormous potential of fecal microbiota transplantation (FMT) might be a promising therapeutic strategy to alter and/or repair the composition of gut microbiota [ 34 ]. It has been shown that FMT can effectively cure patients with IRAEs [ 35 ]. A favorable microbiota might have the potential to ameliorate IRAEs [ 36 ].…”
Section: How To Manage the Iraesmentioning
confidence: 99%